Perspective Research Progress in Cold Responses of Capsella bursa-pastoris - Noman, Ali; Kanwal, Hina; Khalid, Noreen; Sanaullah, Tayyaba; Tufail, Aasma; Masood, Atifa; Sabir, Sabeeh-ur-Rasool; Aqeel, Muhammad; He, Shuilin (Frontiers in Plant Science, 2017)
Plants respond to cold stress by modulating biochemical pathways and array of molecular events. Plant morphology is also affected by the onset of cold conditions culminating at repression in growth as well as yield reduction. As a preventive measure, cascades of complex signal transduction pathways are employed that permit plants to endure freezing or chilling periods. The signaling pathways and related events are regulated by the plant hormonal activity. Recent investigations have provided a prospective understanding about plant response to cold stress by means of developmental pathways e.g. moderate growth involved in cold tolerance. Cold acclimation assays and bioinformatics analyses have revealed the role of potential transcription factors and expression of genes like CBF, COR in response to low temperature stress. Capsella bursa-pastoris is a considerable model plant system for evolutionary and developmental studies. On different occasions it has been proved that C. bursa-pastoris is more capable of tolerating cold than A. thaliana. But, the mechanism for enhanced low or freezing temperature tolerance is still not clear and demands intensive research. Additionally, identification and validation of cold responsive genes in this candidate plant species is imperative for plant stress physiology and molecular breeding studies to improve cold tolerance in crops. We have analyzed the role of different genes and hormones in regulating plant cold resistance with special reference to C. bursa-pastoris. Review of collected data displays potential ability of Capsella as model plant for improvement in cold stress regulation. Information is summarized on cold stress signaling by hormonal control which highlights the substantial achievements and designate gaps that still happen in our understanding.